2019
DOI: 10.17306/j.afs.0636
|View full text |Cite
|
Sign up to set email alerts
|

The influence of additives on frozen snakehead fish surimi and the application of transglutaminase to fish cakes

Abstract: Background. The co-product of cultured snakehead fish protein extraction is an abundant source of myofibrillar protein, with the potential for application in the processing of frozen snakehead fish surimi. The objective of this study was to determine the influence of additives and incubation time on the quality of surimi and surimi-based products. Materials and methods. Cryoprotectant (a mixture of sucrose and sorbitol at a ratio of 1:1 changed from 2% to 4%), in combination with sodium tripolyphosphate (0.1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For producing fish balls, the main steps were to fillet and separate the fish meat and the mixture of skin and scale. The by-products discarded during processing mainly consisted of head, skin, bone, fins, scales, and viscera, and accounted for 54% of the snakehead fish weight [3]. The huge amount of these by-products caused serious ecological issues.…”
Section: Introductionmentioning
confidence: 99%
“…For producing fish balls, the main steps were to fillet and separate the fish meat and the mixture of skin and scale. The by-products discarded during processing mainly consisted of head, skin, bone, fins, scales, and viscera, and accounted for 54% of the snakehead fish weight [3]. The huge amount of these by-products caused serious ecological issues.…”
Section: Introductionmentioning
confidence: 99%
“…ACTIVA TG-K acts as texture enhancer by forming the ε-(γ-glutamyl) lysine crosslinking of myosin heavy chain during the setting of salted fish paste, thereby contributing to a firmer and more cohesive texture [47]. Similar to previous studies on the use of TGs for improving gel strength [13][14][15][16][17][18], we observed an increase in the gel strength of the developed fish paste cake prototype containing 0.3% and 0.5% ACTIVA TG-K. Even though ACTIVA TG-K improved gel strength at both 0.3% and 0.5% concentrations, considering the manufacturing cost of the fish paste cakes, the optimal ratio of ACTIVA TG-K addition was decided at 0.3%.…”
Section: Discussionmentioning
confidence: 67%
“…Panelists generally rated the appearance, color, flavor, texture, and overall liking of these products at a moderate level [15,16]. Notably, Muoi et al [17] found that the addition of 0.7% TGs significantly enhanced the gel properties of fried fish cakes made from frozen snakehead fish surimi, while dos Santos et al [18] reported improved textural and sensory properties in soy-based hybrid sausages with the addition of 0.25% TGs. In this study, we aimed to enhance the storage characteristics of fish paste cake using high-temperature and high-pressure processing, while minimizing associated decreases in physical properties by incorporating edible TGs.…”
Section: Introductionmentioning
confidence: 99%